Transfer of Cellular Content from the Allogeneic Cell-Based Cancer Vaccine DCP-001 to Host Dendritic Cells Hinges on Phosphatidylserine and Is Enhanced by CD47 Blockade - Haoxiao Zuo (MDPI AG, 2021)
DCP-001 is a cell-based cancer vaccine generated by differentiation and maturation of cells from the human DCOne myeloid leukemic cell line. This results in a vaccine comprising a broad array of endogenous tumor antigens combined with a mature dendritic cell (mDC) costimulatory profile, functioning as a local inflammatory adjuvant when injected into an allogeneic recipient. Intradermal DCP-001 vaccination has been shown to be safe and feasible as a post-remission therapy in acute myeloid leukemia. In the current study, the mode of action of DCP-001 was further characterized by static and dynamic analysis of the interaction between labelled DCP-001 and host antigen-presenting cells (APCs). Direct cell–cell interactions and uptake of DCP-001 cellular content by APCs were shown to depend on DCP-001 cell surface expression of calreticulin and phosphatidylserine, while blockade of CD47 enhanced the process. Injection of DCP-001 in an ex vivo human skin model led to its uptake by activated skin-emigrating DCs. These data suggest that, following intradermal DCP-001 vaccination, local and recruited host APCs capture tumor-associated antigens from the vaccine, become activated and migrate to the draining lymph nodes to subsequently (re)activate tumor-reactive T-cells. The improved uptake of DCP-001 by blocking CD47 rationalizes the possible combination of DCP-001 vaccination with CD47 blocking therapies.